Examining the Effects of Need for Achievement and Locus of Control on Entrepreneurial Intention Through Entrepreneurial Attitude - Abdul Rauf Alwi; Arvita Rachmawaty; Erwin Setiawan (Universitas Negeri Makassar, 2025)
Unemployment remains a persistent challenge in developing economies and has increased the importance of entrepreneurship as a pathway for job creation and economic participation. This study examines the direct and indirect effects of need for achievement and locus of control on entrepreneurial intention, with entrepreneurial attitude serving as a mediating variable. A quantitative explanatory approach was employed to analyze the relationships among the proposed variables. The study involved 103 respondents selected through proportional random sampling from a target population of 600 participants in a higher education setting. The findings indicate that need for achievement, locus of control, and entrepreneurial attitude have significant effects on entrepreneurial intention, both directly and indirectly. The results further suggest that entrepreneurial attitude functions as an important psychological mechanism that strengthens the influence of achievement orientation and perceived personal control on entrepreneurial intention. These findings imply that efforts to foster entrepreneurial intention should not only focus on entrepreneurial knowledge and business skills, but also on strengthening internal motivation, personal control beliefs, and positive attitudes toward entrepreneurship. This study offers practical implications for educators and higher education institutions in designing entrepreneurship development programs that support psychological readiness, decision-making capability, and entrepreneurial orientation. The study also provides a basis for future research to expand the model by incorporating broader variables and more advanced methodological approaches.